Exploring the Effectiveness of Health Administration by Posyandu Cadres: A Case Study in Air Terbit Village, Tapung, Kampar: Menelisik Efektivitas Administrasi Kesehatan Kader Posyandu: Studi Kasus di Desa Air Terbit, Tapung, Kampar - Astri Khoir K (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
The effectiveness of health administration at the Posyandu level is very important in supporting accurate health data recording, monitoring, and service delivery. This study aims to analyze the factors that influence the effectiveness of health administration by Posyandu cadres in Air Terbit Village, Tapung District, Kampar Regency. This study uses a qualitative descriptive design through in-depth interviews, observations, and document review with informants consisting of the Head of the Community Health Center, village officials, and active Posyandu cadres. Data analysis was conducted thematically using the 5M approach (Man, Method, Machine, Material, Money) as well as environmental factors. The results of the study indicate limitations in human resources, lack of administrative training for cadres, conventional implementation methods, and weak cross-program coordination. Facilities, promotional media, and administrative funding are still limited, and public awareness of the importance of health reporting is also low. It is concluded that improving the effectiveness of health administration needs to be carried out through cadre training, digitization of record-keeping, routine supervision, and funding support from the community health centers and village government.